Luar - a language for agile development of NCL templates and documents - Bezerra, Diogo Henrique Duarte; Sousa, Dênio Mariz Timóteo; Souza Filho, Guido Lemos de; Burlamaqui, Aquiles Medeiros Filgueira; Silva, Igor Rosberg de Medeiros (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
In the application's development described in NCL language, we have observed the reuse of some models and document structures, which is possible by repetition of common codes on applications. Thus, we do visualize the need to generalize this kind of development described in NCL. This need has been observed by other developers who are aiming at the possibility of the reuse of structure from some documents. This paper introduces Luar, an authoring language for NCL templates. The Luar language has been conceived through analysis of the applications' behavior for iDTV. Luar has a templates's processor developed with the Lua language and library to maintain and to aggregating template collections, sharing them among developers. The entire template system aims to facilitate the design and development of interactive applications described in NCL using the technique of reuse.